Hypoglycemic effect of extracts of Petai Papan (Parkia speciosa, Hassk) - Jamaludin, Fathaiya; Mohamed, Suhaila (Universiti Putra Malaysia Press, 1993)
The oml administration of the chloroform extract of Parkia speciosa to alloxan-induced diabetic rats produced a significant (p<0.01) decrease in blood glucose levels. The hypoglycemic response was approximately proportional to the square root of the dose given. The hypoglycemic activity of the extract reached a maximum 2-5 hours rifter oral administration of the extract and lasted for at least 24 hours.